"Maxillary lateral incisor partial anodontia sequence": a clinical entity with epigenetic origin - Alberto Consolaro; Maurício Almeida Cardoso; Renata Bianco Consolaro
ABSTRACT The relationship between maxillary lateral incisor anodontia and the palatal displacement of unerupted maxillary canines cannot be considered as a multiple tooth abnormality with defined genetic etiology in order to be regarded as a "syndrome". Neither were the involved genes identified and located in the human genome, nor was it presumed on which chromosome the responsible gene would be located. The palatal maxillary canine displacement in cases of partial anodontia of the maxillary lateral incisor is potentially associated with environmental changes caused by its absence in its place of formation and eruption, which would characterize an epigenetic etiology. The lack of the maxillary lateral incisor in the canine region means removing one of the reference guides for the eruptive trajectory of the maxillary canine, which would therefore, not erupt and /or impact on the palate. Consequently, and in sequence, it would lead to malocclusion, maxillary atresia, transposition, prolonged retention of the deciduous canine and resorption in the neighboring teeth. Thus, we can say that we are dealing with a set of anomalies and multiple sequential changes known as sequential development anomalies or, simply, sequence. Once the epigenetics and sequential condition is accepted for this clinical picture, it could be called "Maxillary Lateral Incisor Partial Anodontia Sequence."